2020
DOI: 10.1182/blood-2020-137083
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2 Receptor for COVID-19 Entry Is Expressed on the Surface of Hematopoietic Stem/Progenitor Cells and Endothelial Progenitors As Well As Their Precursor Cells and Becomes Activated in Nlrp3 Inflammasome-Dependent Manner By Virus Spike Protein - a Potential Pathway Leading to a "Cytokine Storm"

Abstract: Background . The SARS-CoV-2 pandemic, with its high mortality, has become an urgent clinical problem. It is well established that SARS-CoV-2 enters human cells after binding to the angiotensin-converting enzyme 2 (ACE2) receptor and utilizes a spike protein (S) for attachment and entry into the cells, leading to their lysis or damage. This infection damages several organs, including lungs, heart, blood vessels, kidneys, and intestines and may lead to a fatal complication known as a "cytokine storm", which is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Therefore, more studies are needed to address if, in addition to ACE2, spike protein may also activate Nlrp3 inflammasome in TLR4 or CD147-dependent manner. A recent report supports this possibility in the case of TLR4 [7]. In conclusion let's hope that next months will bring answers to all these outstanding yet questions.…”
mentioning
confidence: 81%
“…Therefore, more studies are needed to address if, in addition to ACE2, spike protein may also activate Nlrp3 inflammasome in TLR4 or CD147-dependent manner. A recent report supports this possibility in the case of TLR4 [7]. In conclusion let's hope that next months will bring answers to all these outstanding yet questions.…”
mentioning
confidence: 81%
“…The authors of this study have concluded that human bone marrow cells could be prone to SARS-CoV-2 infection. In support of this hypothesis, they have reported that different human stem cell lineages, such as CD34 + CD133 + lin − CD45 − cells, which may differentiate to HSCs and endothelial progenitor cells (EPCs), CD34 + Lin − CD45 + HSCs and CD34 + CD133 + KDR + CD31 + EPCs, express ACE2 and TMPRSS2 at the gene and protein levels [ 88 ]. In addition, it was observed that the viral spike protein activates NLrp3 inflammasomes in HSCs, which likely triggers their pyroptosis [ 88 ].…”
Section: Sars-cov-2 Infection and Hematopoietic Progenitorsmentioning
confidence: 99%
“…In support of this hypothesis, they have reported that different human stem cell lineages, such as CD34 + CD133 + lin − CD45 − cells, which may differentiate to HSCs and endothelial progenitor cells (EPCs), CD34 + Lin − CD45 + HSCs and CD34 + CD133 + KDR + CD31 + EPCs, express ACE2 and TMPRSS2 at the gene and protein levels [ 88 ]. In addition, it was observed that the viral spike protein activates NLrp3 inflammasomes in HSCs, which likely triggers their pyroptosis [ 88 ]. Post-mortem examination of COVID-19 patients has revealed evidence of direct viral infection of endothelial cells with accumulation of inflammatory cells.…”
Section: Sars-cov-2 Infection and Hematopoietic Progenitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spike protein of SARS-CoV-2 has also been found to activate the NLRP3 inflammasome ( Kucia et al, 2020 ). In another research article, it is reported that in cultured murine alveolar macrophages, ultramicronized palmitoylethanolamide inhibits NLRP3 inflammasome expression and the pro-inflammatory response activated by the SARS-CoV-2 Spike protein ( Del Re et al, 2021 ).…”
Section: Innate Immune Sensors and Recognition Of Sars-cov-2mentioning
confidence: 99%